Right Ventricular Dysfunction and Long-Term Risk of Sudden Cardiac Death in Patients With and Without Severe Left Ventricular Dysfunction. (June 2018) - Naksuk, Niyada; Tan, Nicholas; Padmanabhan, Deepak; Kancharla, Krishna; Makkar, Nayani; Yogeswaran, Vidhushei; Gaba, Prakriti; Kaginele, Pranita; Riley, David C.; Sugrue, Alan M.; Rosenbaum, Andrew N.; El-Harasis, Majd A.; et al.
Abstract : Background: Right ventricular systolic dysfunction (RVD) often coexists with various cardiopulmonary diseases. However, the association between RVD and risk of sudden cardiac death (SCD) has not been well studied. This study examined the risk of SCD associated with RVD in patients with heterogeneous underlying cardiac diseases. Methods: The Mayo Clinic cardiac care unit database included 5463 consecutive patients with complete echocardiographic evaluation to assess right ventricular systolic function and RVD severity. Prospective surveillance follow-up was obtained for all patients. SCD was adjudicated when a malignant ventricular arrhythmia was documented as the primary rhythm leading to death. Results: The prevalence of mild RVD and moderate-severe RVD was 14.9% and 17.1%, respectively. Patients with RVD were more likely to have a history of congestive heart failure, cardiac arrest, pulmonary disease, and lower baseline left ventricular ejection fraction compared with those with normal right ventricular systolic function. During a median follow-up of 14 months, the incidence of SCD was highest in patients with moderate-severe RVD (7.4% versus 4.4% in mild RVD versus 1.6% in normal right ventricular function; P <0.001). After adjustment for baseline characteristics, mild RVD (adjusted hazard ratio, 1.57; P =0.046) and moderate-severe RVD (adjusted hazard ratio, 1.91; P =0.006) were independently associated with an increased risk of SCD. Moderate-severe RVD remained an independent predictor of SCD for patients with left ventricular ejection fraction >35% without or with preexisting implantable cardioverter-defibrillator (adjusted hazard ratio, 4.12; P =0.003 and adjusted hazard ratio, 5.04; P <0.001, respectively). Conclusions: Presence of RVD in patients with a history of preexisting cardiac disease is an independent predictor of SCD irrespective of left ventricular ejection fraction. Abstract : Supplemental Digital Content is available in the text.